BILINGUAL CROSSWORD PUZZLE TO IMPROVE THE STUDENTS’ VOCABULARY ACHIEVEMENT - Duri, Munika; Basuni, Muh. (Jurnal Bahasa Lingua Scientia, 2013)
The objective of this study entitled ?The Use of Bilingual Crossword Puzzle to Improve the Students? Vocabulary Achievement of Fifth Grades in MI Salafiyah ? Selopuro Academic Year 2012-2013? was to find whether or not teaching vocabulary by using Bilingual Crossword Puzzle Game could improve students? vocabulary achievemnt. The study used quasi-experimental with one group pretest posttest design . The population of the study was all of  students in MI Salafiyah Selopuro and the sample of the research was entire fifth grade totally 20 students. Because using one group pretest posttest design, there is no control or experimental group in this study. Data of this research was collected by using pretest and posttest. The collected data were analyzed using t-test formula. The results of the data analysis showed that mean score of pretest was 64,70 and mean score of posttest was 79,40. After analyzing the data of pretest and posttest , the result of  T count  was 3,419 and the T table with df 19 and the significance level at 5% was 1.729. Based on the data analysis above the alternative hypothesis was accepted because the T count was higher than the T table (3,419>1,729). Its meant that teaching vocabulary by using bilingual crossword puzzle game was effetive to improve students? English vocabulary achievement of the fifth grade at MI Salafiyah Selopuro Blitar academic year 2012/2013.